FAKTOR-FAKTOR YANG MEMPENGARUHI WISATAWAN CHINA MELAKUKAN FINTECH PAYMENT DI BALI - Putri Utari Cahyani, Ni Luh; Kusuma Negara, I Made; Suwena, I Ketut (Jurnal IPTA (Industri Perjalanan Wisata); Vol 7 No 2 (2019): Jurnal IPTA (December 2019)DO - 10.24843/IPTA.2019.v07.i02.p08, 2019)
WeChat Pay is a Chinese payment platform that makes it easy for users to make mobile phone payments using the Quick Response Code (QR) technology in cooperating merchants. The purpose is to know the characteristics and factors that influencing Chinese tourists doing payment transactions using WeChat Pay in Bali by taking case studies at Discovery Shopping Mall Kuta, and the sample is Chinese tourist who has made a payment transaction using WeChat Pay at Discovery Shopping Mall Kuta. Sampling technique using purposive sampling on 110 respondents. Data collection techniques were conducted in several ways, including: observation, questionnaires, interview, literature study, and documentation. Data analysis techniques done with several stages, including: validity test, reliability test, and factor analysis. The result is there are seven factors that influence the decision of the China's tourist to make a payment transaction using WeChat Pay at Discovery Shopping Mall, including: (1) ease of various transaction activities, (2) increase efficiency, (3) the cost of charge, (4) ease of using/operation, (5) ease of understanding and learning, (6) improve performance, and (7) user satisfaction. The results of factors analysis is ease of work becomes the most dominant factor. This factor consists of several variables, including: Ease of various transaction activities, improve accessibility, availability of payments, and transaction capabilities.